Rheological and thermophysical properties of model compounds for ice-cream with reduced fat and sugar - Drago Šubarić; Jurislav Babić; Đurđica Ačkar; Borislav Miličević; Mirela Kopjar; Vedran Slačanac (Mljekarstvo)
The aim of this research was to investigate the effect of hydrocolloid carrageenan, native tapioca starch and powdered whey on viscosity and thermophysical properties of model ice-cream mixtures with reduced content of sugar and fat. Measurements were performed immediately after mixture preparation and after two months of storage at -18 °C. Results showed that rheological properties of model ice-cream mixtures with reduced content of sugar and fat can be improved by addition of starch and whey, particularly at low temperatures (0 and -5 °C). Improvement of properties at low temperatures is particularly important for before mentioned group of products, as well as the fact that raw materials used in the recipes are cost effective and have high nutritive value. Two-month storage at -18 °C resulted in increase of rheological parameters of all investigated samples. Freeze and thaw temperatures of model mixtures were not changed significantly after two months of storage. On the other hand, enthalpies of freezing and thawing have after storage in the most cases decreased.